(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
The purpose of this article is to study and provide an overview of the epidemiology, clinical presentation, disposition and outcome of COPD in India, which is one of the most affected countries in the world and contributes significantly to the morbidity and mortality of this disease, to the Emergency physicians as they are the front line force for diagnosing and managing all the emergencies in the hospital.Materials and methods:The current work represents a single institutional retrospective study on epidemiology, clinical presentation, disposition and outcome of COPD carried out in tertiary care teaching hospital,Ahmedabad . The data was obtained from the record of 200 patients and reviewed and analysed from October-2017 to September-2019.Results: The data of 200 patients was collected from the record for this study. COPD was found more common in male and 5th- 6th decade. Smoking and tuberculosis were the major risk factors. COPD patients were most commonly presented with breathlessness, fever and cough. In the patients of COPD, emphysematous changes were found more commonly.